2010
DOI: 10.1021/bi1015716
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Origins of Differential RNA Binding Function in Two dsRBDs from the miRNA “Microprocessor” Complex

Abstract: MicroRNAs (miRNAs) affect gene regulation by base pairing with mRNA and contribute to the control of cellular homeostasis. The first step in miRNA maturation is conducted in the nucleus by the “microprocessor” complex made up of an RNase III enzyme, Drosha, that contains one dsRNA binding domain (dsRBD), and DGCR8, that contains two dsRBDs in tandem. The crystal structure of DGCR8-Core (493–720), containing both dsRBDs, and the NMR solution structure of Drosha-dsRBD (1259–1337) have been reported, but the solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 74 publications
7
41
0
Order By: Relevance
“…This suggests that protein-protein interactions may be mediated by the extended α1-β1 loop of Drosha-dsRBD too. We have previously suggested that the dynamics of Drosha-dsRBD’s extended α1-β1 loop may in some way impair dsRNA binding by the domain [18]. In contrast, our present work shows convincingly that the loss of non-canonical but conserved Region 3 motif sequence in this dsRBD is responsible for its loss of dsRNA binding activity.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…This suggests that protein-protein interactions may be mediated by the extended α1-β1 loop of Drosha-dsRBD too. We have previously suggested that the dynamics of Drosha-dsRBD’s extended α1-β1 loop may in some way impair dsRNA binding by the domain [18]. In contrast, our present work shows convincingly that the loss of non-canonical but conserved Region 3 motif sequence in this dsRBD is responsible for its loss of dsRNA binding activity.…”
Section: Discussionsupporting
confidence: 39%
“…Our laboratory has characterized the structure of an in vitro transcribed pri-mir-16-1 construct [33] and used this model to establish the dsRNA binding affinity of the dsRBDs from DGCR8 [18, 28], TRBP [34], and Dicer [23], as summarized in Table 2. Our results have proven to be highly consistent with those reported by other laboratories using related pri-miRNA constructs [35, 36].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, both Drosha and Dicer function with partner proteins. Drosha forms the microRNA Microprocessor complex with DGCR8 that contains two dsRBDs (Wostenberg et al, 2010). Dicer functions with TRBP and PACT, each of which contains three dsRBDs (Haase et al, 2005; Kok et al, 2007; Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(27). Standard three-dimensional NMR techniques (38) were employed to obtain and confirm backbone assignments for DGCR8 RBD1 (residues 509 -582) (39). Line width and crosspeak intensities of 1 H, 15 N-TROSY experiments at varying protein/RNA ratios were determined using Sparky, assuming Gaussian line shapes (31 31 P) room temperature probe with triple-axis shielded gradients.…”
Section: Methodsmentioning
confidence: 99%